Strategic Step for Environmental Rescue: A Theoretical Legal Studies - Bambang Sutrisno (Universitas Muhammadiyah Sidoarjo, 2014)
Indonesia is among the developing countries that are struggling to develop in the field of industrial development. The logical consequence of any development process, especially industrial development is the emergence of associated impacts that greatly affect the durability and sustainability of the environment. Developing the equitable industry in order to create public welfare is important. However, maintaining the security and preservation of the environment is also very important, because it is only with the availability of a good environment and healthy living that human beings can perform daily living. The availability of good and healthy environment is the constitutional responsibility of the government, as well as part of the human rights of all citizens which must be given by the State. Efforts to create a good environment and healthy living will be effective if controlled by State government and institutions who understand the objective conditions on the ground. In this regard, the granting of the authority on environmental control to regional government autonomously is the right, very smart policy choice. How To Cite: Sutrisno, B. (2014). Strategic Step for Environmental Rescue: A Theoretical Legal Studies. Rechtsidee, 1(1), 27-58. doi:http://dx.doi.org/10.21070/jihr.v1i1.98